Handbook of communication and social interaction skills - Greene, John O., 1954-; Burleson, Brant Raney, 1952- (LEA's communication series., 2003)
Providing a thorough review and synthesis of work on communication skills and skill enhancement, this Handbook serves as a comprehensive and contemporary survey of theory and research on social interaction skills. Editors John O. Greene and Brant R.